LINEAR TYPE ACTUATOR - MATSUSHITA KUNITAKE; FUJITANI SAKAE; HARADA NAOYUKI; SUZUKI YUZURU (2005)
In order to reduce cost through reduction in material cost and improvement of productivity, in a linear type actuator comprising: a stator unit having coils consisting of wound magnet wires and housed inside stator sub-assemblies and pole teeth arranged on the inner circumference thereof; a rotor unit having a field magnet arranged on the outer circumference thereof and rotatably disposed so as to oppose the pole teeth with a given gap; an output shaft attached to a center portion of the rotor unit and movble in the axial direction thereof; and converting means provided on the innermost diametral circumferential surface of the rotor unit and adapted to convert rotary motion of the rotor unit into linear motion of the output shaft, the converting means is made of a material different from that of the rotor unit.